Assessment of mean platelet volume in chronic obstructive pulmonary disease during stable period and acute exacerbation. Issue 4 (2013) - Erden, Ersin Şükrü; Dokuyucu, Recep; Demirköse, Mesut; Yengil, Erhan; Sefil, Fatih; Bilgiç, Hatice Kayım; Doğru, Sibel; Motor, Sedat
No abstract available